The Impact of Changing Consumer Behaviour on Market Analysis Techniques - Yue, Xiang (Transactions on Economics, Business and Management Research, 2024)
This thesis explores the impact of changing consumer behaviour on market analysis techniques and analyses the role of technological advances, socio-cultural changes and economic factors in driving the evolution of market analysis tools and methods. With the development of big data, artificial intelligence and machine learning technologies, market analysis has become more accurate and efficient. The widespread use of social media and online behavioural analytics has driven personalisation and precision marketing, while real-time data and predictive analytics have helped companies become more agile in responding to market changes. This thesis also discusses the importance of privacy protection and data security, as well as the fact that future research should focus on technological advances, data ethics and the diversity of consumer needs in order to respond to the changing market environment. The study suggests that the continuous evolution of market analytics will lead to deeper consumer insights and more competitive market strategies for businesses.